SMART GRID ENABLER (SGE) FRAMEWORK DEVELOPMENT FOR RESIDENTIAL SECTOR TOWARDS ENERGY CONSERVATION STRATEGIES VIA FUZZY DELPHI METHOD - Abdul Razak, Ahmad Haqqi Nazali; Ahmad, Nur Azfahani; Sukki, Firdaus Muhammad; Radin Abdul Halim, Radin Zulhazmi (Journal of Civil Engineering, Science and Technology, 2025)
The global implementation of smart grids has revolutionised the electricity grid, including in Malaysia, where Tenaga Nasional Berhad leads the initiative. This Smart Grid system is akin to the internet of electricity, serving as a pivotal element in the sustainable energy transition within the electricity sector. The residential sector, which heavily relies on electricity for daily activities, stands to benefit significantly from this development. Despite the numerous advantages offered by smart grids, the Malaysian residential sector has not yet fully optimised these benefits to incorporate fit-for-use components. Thus, this research aims to develop a Smart Grid Enabler (SGE) framework for the Malaysian residential sector that supports energy conservation strategies. Based on the Trias Energetica and Smart Grid Conceptual Model, the Fuzzy Delphi Method is utilised to synthesise expert consensus and establish critical components for the SGE framework and achieve the aim of this research. Subsequent future research anticipates a better refined SGE framework which explores pragmatic and practical real-world applications in the residential setting. This study contributes to ongoing efforts in sustainable energy development through smart grid system optimisation for the Malaysian residential sector.